2010
DOI: 10.1155/2010/130636
|View full text |Cite
|
Sign up to set email alerts
|

AMP-Activated Protein Kinase Activation during Cardioplegia-Induced Hypoxia/Reoxygenation Injury Attenuates Cardiomyocytic Apoptosis via Reduction of Endoplasmic Reticulum Stress

Abstract: Cardioplegic-induced H/R injury results in cardiomyocytic apoptosis. AMPK has been shown to reduce ER stress and the unfolded protein response (UPR). Whether AMPK activation can attenuate cardiomyocytic apoptosis after cardioplegia-induced H/R injury is unknown. Cardiomyocytes were exposed to simulated ischemia by incubation in a hypoxic chamber with intermittent cold cardioplegia solution infusion at 20-minute intervals and subsequently reoxygenated in a normoxic environment. Various doses of AMPK activators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 42 publications
5
42
0
Order By: Relevance
“…It has been reported to reduce endoplasmic reticulum stress. 44 Endoplasmic reticulum stress has been shown to be involved in vascular calcification. 45 Also, metformin activates both AMPKα1 and AMPKα2.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to reduce endoplasmic reticulum stress. 44 Endoplasmic reticulum stress has been shown to be involved in vascular calcification. 45 Also, metformin activates both AMPKα1 and AMPKα2.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain such cardioprotection by metformin, including lessening endoplasmic reticulum stress, inhibition of cellular unfolded protein response, eNOS activation and increased expression of PGC-1α, a key controller of energy metabolism in muscle, which is down-regulated in diabetic conditions [79][80][81].…”
Section: Metformin and CV Diseasementioning
confidence: 99%
“…Some studies also link hypoxia/reoxygenation exposure to ER stress. For example, it has been shown that hypoxia/reoxygenation injury could induce cardiomyocytic apoptosis via activation of ER stress (66). Caspase-12 and C/EBP homologous protein (CHOP), two marker proteins of ER stress, were also upregulated under hypoxia/reoxygenation conditions (43).…”
Section: Introductionmentioning
confidence: 99%